Epidemiological characteristics of acute dehydrating diarrhea during an epidemic of cholera: a study from North India - Shah, Mohd Y.; Shah, Faisal Y.; Kitab, Ifrah S.; Shah, Faizan Y. (International Journal of Research in Medical Sciences, 2020)
Background: Cholera is an acute diarrheal disease which continues to be a public health problem since inception. It is a disease related to poverty, overcrowding, poor sanitation and inaccessibility to clean water. India forms a fertile ground for the sustenance and transmission of cholera. However the diagnosis of cholera doesn’t easily come to mind when dealing with cases of dehydrating diarrheas. Methods The study was a prospective cohort study conducted in a tertiary care center of North India. All patients presenting to the medicine department of this hospital with acute dehydrating diarrhea were enrolled for the study. Stool samples for hanging drop test and culture were sent in all patients to rule this cholera. Results: Eighty four patients presenting to the medicine department of this hospital with acute dehydrating diarrhea were included in this study. All the patients had loose watery stools but classical rice water stools were seen in only 20.2% of patients. Patients with rice water stools were more likely to be positive for stool culture (70.6%, n = 12/17) and hanging drop preparations (82.3%, n = 14/17) as compared to those with watery stools. The difference was found to be statistically significant for culture (70.6% vs 40.3%, p-value = 0.02) as well as hanging drop preparation (82.3% vs 47.8%, p-value = 0.01). Conclusions: The prevalence of culture positive cholera cases was found to be 46.4% out of all the cases presenting with acute dehydrating diarrhea which is quite high. Rice water stools which are considered characteristic for cholera were found in less than half of culture positive cases of cholera (43.6%, n = 17/39). Hanging drop preparation was found to have a sensitivity of 87.2% and a specificity of 86.5% in comparison to stool culture which is regarded as gold standard for diagnosis of cholera. Cholera may be considered as an ongoing epidemic with periodic surge in cases and should be suspected whenever cases of acute watery diarrhea present in increased numbers with features of severe dehydration, especially when the cases are clustered together and from a poor socio-economic background.